ANALISIS STRATEGI PENGELOLAAN PASAR TRADISIONAL â€œBANGSRIâ€ DI DINAS KOPERASI, UMKM DAN PENGELOLAAN PASAR KABUPATEN JEPARA - Widyasari, Ferninda Arlisa; Yuniningsih, Tri (Journal of Public Policy and Management Review, 2016)
Traditional market one of economic growth proponent aspect in Jepara Regency. But, the condition of Bangsri Traditional Market shown the unstable year by year, those are so many lack of the infrastructures for the public (merchants and consumer). The aim of this research is to formulate a strategy that must be done by Department of Cooperation, UMKM and Market Management of Jepara Regency to increase the management in Bangsri Traditional Market. This research used a qualitative descriptive study. The techniques of collecting data is documentation, interview, observation and literature study. This research used purposive sampling and accidental sampling method to determine the informants. The writer identified the internal and external factors of organization by using SWOT analysis, then will be gained strategic issue. Next step is measuring priority scale by using Litmus Test to know the most strategic issue. The result of this research showed that the management strategic in Bangsri Traditional Market has not been optimal yet, thus it needs new strategy to solve them. The recommended strategy is to make the optimum cooperation with stakeholders and private to increase Bangsri Traditional Market management, raise the merchants participation by socialization to manage Bangsri Traditional Market, strive for the infrastructures in Bangsri Traditional Market and coordination between Department, Government, regional legislative assembly, market organizer and merchants to increase the donation for Bangsri Traditional Market.